The Impact of Corona Virus Infection on Economy of Russia in General and on Certain Regions of the Country (illustrated by the Krasnodar area) - I. V. Balashova; T. A. Tereshchenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
A great number of enterprises of small and medium business (SMB) and a big variety of company specializations increase competitiveness of economy. A serious drop in the number of micro- and small enterprises in 2020 with a simultaneous increase in the number of medium enterprises testify to the fact that some organizations ceased their work, while others, on the contrary, integrate in order to expand and reach a new level of economic development. As 2020 was marked by the period of the corona virus infection, some organizations took a decision to merge and change their specialization to such area that were supported by the government during the pandemic to continue their business in such a complicated situation thanks to the state aid. In general, a key reason for cutting the number of SMB entities during this period is restrictive measures introduced in 2020 due to the corona virus infection. A lot of enterprises suffered losses during the pandemic and were forced to stop working. Recommendations worked out by the author on the basis of research findings can produce a favorable impact on the development of economic potential of small business enterprises.